Factors Affecting Customer Satisfaction towards Supermarket (In association with Bhat-Bhateni Supermarket and Departmental store) - Chand, Prayag (Brixton Scholarly Review, 2025)
Customer satisfaction is a measure of how well a company's products or services meet or exceed customer expectations. It reflects the customer's overall contentment with their experience, including factors such as product quality, service quality, price, and the ease of the purchasing process. Customer satisfaction leads to customer loyalty, retention, positive word of mouth, employee satisfaction, and increased profit. It also prevents negative word of mouth and increases customer feedback, which benefits the firm. Thus, customer satisfaction is crucial for supermarkets to retain customers and build loyalty. This study was conducted with the main objective of determining the most significant and least significant factors affecting the satisfaction level of customers, as well as providing suggestions based on the study's findings. The research uses a conceptual framework developed from a literature review, and the variables used to determine the level of satisfaction are location, facilities, product quality, reliability, customer service, method of payment, and process. The research employs descriptive analysis, i.e., mean, and non-probability convenience sampling method. The sample size used in this research is 50, and the primary data collection tools are survey questionnaires and interviews. The result of the study shows that the overall level of satisfaction among the respondents is moderate. The significant factors for customer satisfaction are price, quality, and location, whereas customer service is less significant for customer satisfaction. The insights regarding the level of customer satisfaction within supermarkets highlight the need to focus on customer retention strategies by enhancing service quality and personalization. After segmenting the market and customizing the products, supermarkets can realize an increase in customer loyalty and ease of purchase. Ultimately, customer satisfaction needs to be given prime attention, as it will build a competitive edge and ensure business sustainability within a competitive environment.